PROBLEMATIKA IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN PAI - Zerlina Syahda, Aisha; Wahyuningsih, Diah (LPPM STAI Muhammadiyah Probolinggo, 2024)
In education in Indonesia, the curriculum is an important component to support the success of the learning process. PAI learning is also adjusted to the new curriculum, namely the Merdeka Curriculum. The purpose of this study is to find out how the problematic implementation of Merdeka Curriculum in PAI learning. The method chosen in this study uses Systematic Literature Review (SLR) by reviewing several articles selected according to the theme taken from 2022-2024 and then analyzed first. The results of the analysis show that the problematic implementation of the Merdeka Curriculum occurs in several aspects including: 1) teacher competence in adapting, 2) the diversity of students' backgrounds, 3) the government provides less direction, 4) insufficient facilities, 5) a large administrative burden on teachers.